2018
DOI: 10.1097/iae.0000000000001879
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Structural Changes and Vascularity Index in Stargardt Disease on Swept Source Optical Coherence Tomography

Abstract: Choroidal vascularity index appears to be a more robust tool compared with SFCT for choroidal changes in Stargardt disease. Choroidal vascularity index can possibly be used as a surrogate marker for disease monitoring. A decrease in CVI was associated with a decrease in visual function in eyes with Stargardt disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…Choriocapillaris loss in STGD has also been shown in prior OCTA studies. [42][43][44][45][46][47] Battaglia Parodi, et al, showed that CCVD was worse in STGD eyes that had chorioretinal atrophy, 46 and both Pellegrini, et al, and Muller, et al, found that the choriocapillaris flow signal was visibly diminished within areas of RPE atrophy in STGD, but not outside the areas of RPE atrophy. 42,47 Similar to these prior studies, the CCVD within areas of isolated RPE atrophy in our STGD patients was significantly lower than normal, but we also showed the same thing in areas of isolated IS/OS loss.…”
Section: Discussionmentioning
confidence: 99%
“…Choriocapillaris loss in STGD has also been shown in prior OCTA studies. [42][43][44][45][46][47] Battaglia Parodi, et al, showed that CCVD was worse in STGD eyes that had chorioretinal atrophy, 46 and both Pellegrini, et al, and Muller, et al, found that the choriocapillaris flow signal was visibly diminished within areas of RPE atrophy in STGD, but not outside the areas of RPE atrophy. 42,47 Similar to these prior studies, the CCVD within areas of isolated RPE atrophy in our STGD patients was significantly lower than normal, but we also showed the same thing in areas of isolated IS/OS loss.…”
Section: Discussionmentioning
confidence: 99%
“…Ratra et al showed that CVI was significantly reduced in SD as compared to normal eyes and that the reduction of CVI was correlated with worsening of visual acuity [25]. They suggested that this novel parameter appears to be a more sensitive biomarker in detecting choroidal changes as compared to subfoveal CT.…”
Section: In Inherited Retinal Disordersmentioning
confidence: 99%
“…Swept-source optical coherence tomography (SS-OCT) uses a longer wavelength than spectral domain OCT, penetrates tissues better and enables us to visualise the choroid 3 . Choroidal changes are evaluated in various systemic 4 and ocular [5][6][7][8][9][10][11] disorders.…”
Section: Introductionmentioning
confidence: 99%